A scientometric review of the growing trends in transcranial alternating current stimulation (tACS) - Liu, Yuanli; Luo, Yulin; Zhang, Na; Zhang, Xiaochu; Liu, Shen (Frontiers in Human Neuroscience, 2024)
The aim of the current study was to provide a comprehensive picture of tACS-related research in the last decade through a bibliometric approach in order to systematically analyze the current status and cutting-edge trends in this field.Methods: Articles and review articles related to tACS from 2013 to 2022 were searched on the Web of Science platform. A bibliometric analysis of authors, journals, countries, institutions, references, and keywords was performed using CiteSpace (6.2.R2), Vosviewer (1.6.19), Scimago Graphica (1.0.30) and Bibliometrix (4.2.2).Results: A total of 602 papers were included. There was an overall increase in annual relevant publications in the last decade. The most contributing author was Christoph S. Herrmann. Brain Stimulation was the most prolific journal. The most prolific countries and institutions were Germany and Harvard University, respectively.The findings reveal the development prospects and future directions of tACS and provide valuable references for researchers in the field. In recent years, the keywords "gamma", "transcranial direct current simulation", and "alzheimer's disease" that have erupted, as well as many references cited in the outbreak, have provided certain clues for the mining of research prefaces. This will act as a guide for future researchers in determining the path of tACS research.